A Novel "Slit Side View" Method to Evaluate Fluid Dynamics during Phacoemulsification. (27th September 2018) - Suzuki, Hisaharu; Igarashi, Tsutomu; Shiwa, Toshihiko; Takahashi, Hiroshi
Abstract : Due to recent technical advances in cataract surgeries, there has been a significant improvement in the safety and surgical outcomes of phacoemulsification. However, the corneal endothelium can be damaged during phacoemulsification by multiple factors. Therefore, we used a slit lamp to analyze the fluid dynamics of ophthalmic viscosurgical devices (OVDs) in the anterior chamber during phacoemulsification. In this experimental study, extracted porcine eyes were injected with OVDs stained with fluorescein through a side port of the eye and then fixed on a slit lamp microscope. After inserting a phaco tip, phacoemulsification simulation was then performed on the iris plane. Subsequent movements of OVDs in the anterior chamber were observed during the procedure by using a slit lamp microscope. Aspiration and removal of cohesive OVDs from the inside of the anterior chamber occurred within a few seconds after the ultrasonic vibration. Aspiration of dispersive OVDs occurred gradually, with some of the OVDs remaining on the side of the anterior chamber side in an irregular shape. This shape enabled the OVD to trap the air, thereby preventing the air from directly touching the corneal endothelium. Viscoadaptive OVDs remained inside the anterior chamber as a lump, with the infusion solution flowing between the corneal endothelium and the OVD, thus leading to the eventual aspiration of the OVD. Viscous dispersive OVDs remained as a lump between the corneal endothelium and the phaco tip. However, once the infusion solution flowed between the cornea and the OVD, the OVD detached from the corneal endothelium, indicating that this type would likely be aspirated and removed. This method, termed the "slit side view, " enables viewing of the movement of OVDs during surgery, as well as observation of the fluid dynamics in the anterior chamber.